A Retrospective Study on Correlation of Facial Fractures and Type of Trauma in Patients Admitted in Department of Maxillofacial Surgery of Stomatology National and Specialized Hospital, Kabul, Afghanistan - Sharif AK; Ehsan H; Mirzad SW; Ibrahimkhil MA (Clinical, Cosmetic and Investigational Dentistry)
Abdul Karim Sharif,1,2 Hedayatullah Ehsan,2,3 Sayed Wahabuddin Mirzad,1 Munir Ahmad Ibrahimkhil2,3 1Department of Maxillofacial Surgery, Stomatology National and Specialized Hospital, Kabul, Afghanistan; 2Faculty of Medicine and Dentistry, Kabul University of Medical Sciences “Abu Ali Ibn Sina”, Kabul, Afghanistan; 3Medical Sciences Research Center, Ghalib University, Kabul, AfghanistanCorrespondence: Abdul Karim Sharif, Department of Maxillofacial Surgery, Stomatology National and Specialized Hospital, Kabul, Afghanistan, Tel +0093781194934, Email Sharif.abdulkarim@gmail.comBackground: Facial bone fractures represent a significant clinical challenge due to their prevalence and the complexity of treatment required. Understanding the demographic patterns, causes, and treatment outcomes of these injuries is crucial for improving patient care and developing targeted prevention strategies.Objective: This study aims to analyze the demographic characteristics, etiological factors, anatomical distribution, and treatment modalities of patients presenting with facial bone fractures at Stomatology National and Specialized Hospital in Kabul, Afghanistan, during 2022.Methods: A retrospective analysis was conducted on 463 patients with facial bone fractures treated at the hospital. Data collected included patient demographics, causes of trauma, fracture location, and treatment methods. Statistical analysis was performed to identify patterns and correlations.Results: The study included 463 patients (378 males and 85 females), aged between 3 and 88 years, with a mean age of 26.34 years. The primary causes of trauma were road traffic accidents (RTAs) (29.6%), interpersonal violence (26.1%), and falls (23.3%). The mandible was the most commonly fractured bone (74.1%), with the parasymphysis being the predominant site of injury. Treatment predominantly involved closed reduction (54.9%), with a significant portion of patients undergoing open reduction and internal fixation (ORIF) (45.1%).Conclusion: The findings highlight RTAs, interpersonal violence, and falls as the leading causes of facial bone fractures. The mandible is the most frequently affected bone. Closed reduction remains the most common treatment modality. These insights underline the need for enhanced preventive measures, including stricter enforcement of traffic regulations and targeted interventions to address interpersonal violence and fall prevention.Keywords: Afghanistan, closed reduction, epidemiology, facial bone fractures, interpersonal violence, open reduction and internal fixation, road traffic accidents